Teachers’ perspectives on bullying in schools: a comparative mixed methods study in England and the United States - Hurtubise, P (2020)
Teachers play a critical role in responding to, reporting, and preventing bullying. This study focuses on teachers’ perceptions of various types of bullying: physical, verbal, relational, and especially the more recent phenomenon of cyberbullying. It compares English and US teachers’ perspectives of the seriousness of these different types of bullying, thereby investigating how and why teachers have different views of how to address bullying and the different reasons they give as to why they would or would not respond to different bullying scenarios. This can possibly contribute to potential strategies to combat bullying.